ANALISIS OVERREACTION PASAR PADA SAHAM WINNER DAN LOSER DI BURSA EFEK INDONESIA - Pratama, I Gede Surya; Purbawangsa, Ida Bagus Anom; Artini, Luh Gede Sri (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.05.NO.12.TAHUN 2016, 2016)
This research can give due consideration to investor in making an investment decision in order not react to overreaction of market information. The research objective test overreaction in the stock market winner and loser in the Indonesia Stock Exchange 2014. This research is a comparative study using secondary data. The population in this study were 141 companies and samples obtained after do a purposive sampling method are 137 manufacturing companies in 2014. This study uses abnormal return as research variables. The market model is used as a method to calculate the expected return. Statistical test used in this study was independent sample t-test, to test for differences in average abnormal return of winner and loser. The results based on hypothesis testing showed that there was no statistically significant overreaction in manufacturing companies in 2014, that proven by winner abnormal returns stock is bigger than the loser abnormal returns return, significantly.
Keywords: Market Efficiency, Manufacturing, Abnormal Return, Overreaction.